2000
DOI: 10.1002/1521-3757(20001201)112:23<4454::aid-ange4454>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Regiospecificity of Cleavage in FeIII Catecholate Complexes: Tridentate Facial versus Meridional Ligands

Abstract: Der Koordinationsmodus bestimmt die Regiospezifität: Ein facialer dreizähniger Ligand ermöglicht es bei Eisen‐Brenzcatechinat‐Komplexen (siehe Schema), dass O2 in Nachbarschaft zum Brenzcatechin‐Dianion an das Eisenzentrum koordiniert und es dann so angreifen kann, dass eine Spaltung der C2‐C3‐Bindung erfolgt („Extradiol‐Spaltung“). Meridionale dreizähnige Liganden haben dagegen eine Spaltung der C1‐C2‐Bindung („Intradiol‐Spaltung“) zur Folge oder aber die 1,2‐Chinon‐Bildung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…These results imply that the O 2 -incorporation into the aryl ring is through a single-oxygen insertion rather than the insertion of both oxygen atoms of the O 2 as proposed earlier [33,55,58,61,62,63,64]. This incorporation of a single oxygen atom from O 2 is analogous to the reaction of oxygenases in biological systems (Scheme 9c), which leads to distinct intradiol or extradiol ring-opening products, respectively, depending on the initial sites of O 2 coordination [66,67,68,69]. It is expected that the activation and insertion of O 2 into aromatic ring in the present case is dependent on its coordination to the Ti–sites on the TiO 2 surface, just as in the active centre of oxygenases.…”
Section: Photocatalytic Cleavage Of Aryl-ring On Tio2 Surfacesupporting
confidence: 63%
“…These results imply that the O 2 -incorporation into the aryl ring is through a single-oxygen insertion rather than the insertion of both oxygen atoms of the O 2 as proposed earlier [33,55,58,61,62,63,64]. This incorporation of a single oxygen atom from O 2 is analogous to the reaction of oxygenases in biological systems (Scheme 9c), which leads to distinct intradiol or extradiol ring-opening products, respectively, depending on the initial sites of O 2 coordination [66,67,68,69]. It is expected that the activation and insertion of O 2 into aromatic ring in the present case is dependent on its coordination to the Ti–sites on the TiO 2 surface, just as in the active centre of oxygenases.…”
Section: Photocatalytic Cleavage Of Aryl-ring On Tio2 Surfacesupporting
confidence: 63%
“…Proposals have ranged from first-sphere effects such as the oxidation state of the iron, or the vastly different endogenous ligand sets, to outer sphere effects from second-sphere residues and to the orientation of the alkylperoxy bond with respect to the cleaved C–C bond. Regarding the metal oxidation state, model studies have shown both Fe II and Fe III complexes are capable of both extradiol and intradiol cleavage. Early mechanistic studies of the intradiol and extradiol dioxygenases using alternative substrates and other chemical probes lead to the idea that the coplanar alignment of the peroxo O–O bond with the scissile C–C bond (inspired by the Criegee rearrangement for alkylperoxides) dictates the cleavage regiospecificity. , Some of the first computational studies supported this proposal. , More recently, significant advances have come from the trapping, spectroscopic and crystallographic characterization of key enzyme intermediates in the reaction cycles. Of these studies, two crystallographic intermediates are particularly notable. In-crystallo reaction of the EDO, homoprotocatechuate 2,3-dioxygenase (HPCD) with the slow 4-nitrocatechol (4NC) substrate and dioxygen resulted in an Fe-O 2 -4NC intermediate assigned as an Fe II -peroxy-quinone species, which forms after initial O 2 -activation but prior to catechol cleavage .…”
Section: Introductionmentioning
confidence: 99%